PRINCIPAL'S COMMUNICATIVE STRATEGY IN HANDLING TEACHER CONFLICT TO IMPROVE HARMONIZED RELATIONSHIP IN SCHOOL ENVIRONMENT - Nur Kholis Usman; Yuliani; Mi'at; Khairul Efendi; Ahmad Suriansyah; Ratna Purwanti (Universitas PGRI Palembang, 2025)
Conflicts among teachers in a school setting are a natural occurrence, often arising from differing viewpoints and individual traits. The principal's role in managing these conflicts through effective communication is vital in maintaining a harmonious and supportive work environment. This research investigates the communicative strategies applied by the principal of SD Negeri 2 Pantai in resolving teacher conflicts and fostering relational harmony within the school. Using a case study approach, data were gathered through interviews, observation, and document review. The results show that strategies such as open dialogue, mediation, and the promotion of a collaborative work culture significantly contribute to minimizing conflicts while boosting teacher motivation and teamwork. The study recommends that school principals enhance their communication and conflict resolution competencies to create a more positive and harmonious school climate.